FOSTERING CREATIVE THINKING SKILLS IN PROSPECTIVE ELEMENTARY SCHOOL TEACHERS: DEVELOPING TEACHING MATERIALS BASED ON THE PROJECT-ORIENTED TPACK APPROACH - Wiryanto; Ali Fakhrudin, Heru Subrata, Suprayitno, Helda Kusuma Wardani (Adisam Publisher, 2026)
The results of the preliminary study show that the creative thinking skills of prospective elementary school teacher students are relatively low, especially in designing technology-based learning that is to the needs of the 21st century. Therefore, this study aims to develop project-oriented TPACK (Technological Pedagogical Content Knowledge)-based teaching materials to improve the creative thinking skills of elementary school teacher education students. This study used a research and development (R&D) method adapted from Borg & Gall. The subjects of the study consisted of 128 elementary school teacher education students involved in learning planning for elementary schools. The study results show that project-oriented TPACK-based teaching materials are valid, practical, and effective. Experts have confirmed that the teaching materials are valid in construction and content. In addition, observations of increasing student activity at each meeting indicate that the teaching materials are applied practically in learning planning. The students' creative thinking skills test results show that these teaching materials effectively improve the creative thinking skills of prospective teachers. This study implies that using the proper method can improve students' creative thinking skills to design various alternative solutions to problem-solving in learning. This study suggests further developing project-oriented TPACK-based teaching materials for elementary school students.